Penerapan Model Project Based Learning untuk Meningkatkan Kemampuan Cerita Anak pada Pelajaran Bahasa Indonesia - Nurfita, Nurfita (Fakultas Sastra Universitas Muslim Indonesia, 2023)
This study aims to describe the application of the Project Based Learning model to improve children's story skills in Indonesian language lessons at SDI Mallengkeri Bertingkat I, Makassar City. This type of research is Classroom Action Research. The students who were the subject of the research were 31 grade IV students. Data obtained from research results through instruments will be processed and analyzed using descriptive statistical data analysis. The results of students' Indonesian learning can be seen from their speaking skills individually and in groups. The criteria for a student are said to be complete when they meet the specified Minimum Completeness Criteria. The criteria for completeness of student learning outcomes are said to be complete if they meet the minimum completeness criteria determined by the school, namely 70, while classical completeness is achieved if at least 80% of students in the class have achieved a minimum score of completeness. The results showed that the process of learning children's stories in cycle I was unsatisfactory and the classroom atmosphere was still not conducive, students' interest in participating in learning was lacking, because cycle I was not successful, so the researcher continued his research in cycle II. After the implementation of cycle II, the improvement in learning greatly increased, students began to be active and enthusiastic about participating in learning, the classroom atmosphere was conducive and the grades obtained by students increased. The aspects that are considered and assessed in this lesson are the courage of students to express opinions, group cooperation, pretest and posttest. ABSTRAK: Penelitian ini bertujuan untuk mendeskripsikan penerapan model Project Based Learning untuk dalam meningkatkan kemampuan cerita anak pada pelajaran bahasa Indonesia di SDI Mallengkeri Bertingkat I Kota Makassar. Jenis penelitian ini adalah Penelitian Tindakan Kelas. Siswa yang menjadi subjek penelitian adalah siswa kelas IV yang berjumlah 31 siswa. Data yang diperoleh dari hasil penelitian melalui instrumen akan diolah dan dianalisis menggunakan analisis data statistik deskriptif. Hasil belajar bahasa Indonesia siswa dapat dilihat dari keterampilan berbicara secara individual maupun kelompok. Kriteria seorang siswa dikatakan tuntas ketika memenuhi Kriteria Ketuntasan Minimal (KKM) yang ditentukan. Kriteria ketuntasan hasil belajar siswa dikatakan tuntas apabila memenuhi kriteria ketuntasan minimal yang ditentukan oleh sekolah yaitu 70, sedangkan ketuntasan klasikal tercapai apabila minimal 80% siswa di kelas tersebut telah tercapai skor ketuntasan minimal. Hasil penelitian menunjukkan bahwa proses pembelajaran cerita anak pada siklus I kurang memuaskan dan suasana kelas yang masih kurang kondusif , minat siswa dalam mengiuti pembelajaran pun kurang , dikarenakan pada siklus I ini belum berhasil maka penelliti melanjutkan penelitiannya ke siklus II. Setelah pelaksanaan siklus II maka peningkatan pembelajaran sangat meningkat, siswa mulai aktif dan semangat mengikuti pembelajaran suasana kelas pun kondusif dan nilai yang di peroleh siswa meningkat. Aspek yang diperhatikan dan dinilai dalam pembelajaran ini adalah keberanian siswa menyampaikan pendapat, kerjasama kelompok, tes pretest dan posttest.